2012
DOI: 10.1159/000338383
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Anti-Quorum-Sensing Activity of Fermentation Metabolites from Different Strains of a Medicinal Mushroom, Phellinus igniarius

Abstract: Aims: This study aimed to evaluate the different abilities of various Phellinus igniarius strains inhibiting quorum sensing (QS), to search for novel QS inhibitors from them and to analyze their inhibitory activity, with a view to their possible use in controlling infections. Methods: The bioactive metabolites produced by P. igniarius cultures were tested for their abilities to inhibit QS-regulated behavior. All P. igniarius strains were cultured in potato-dextrose medium by large-scale submerged fermentation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Some fungi produce quorum-quenching compounds such as patulin and penicillic acid from Penicillium spp., which can suppress bacterial biofilm formation [68]. Other studies reported that the extracts of Fusarium graminearum , Lasidiplodia sp., Phellinus igniarius , and fruiting bodies of Auricularia auricular , Tremella fuciformis , and Ganoderma lucidum have QS inhibitory activity [69,70,71,72,73,74]. Fungal QSIs were reported in the genera Penicillium and Trichoderma : polyhydroxyanthraquinones, penicillic acid, and patulin from P. restrictum , P. radicicola , and P. coprobium , respectively [68,75]; and carot-4-en-9,10-diol from T. virens [76].…”
Section: Resultsmentioning
confidence: 99%
“…Some fungi produce quorum-quenching compounds such as patulin and penicillic acid from Penicillium spp., which can suppress bacterial biofilm formation [68]. Other studies reported that the extracts of Fusarium graminearum , Lasidiplodia sp., Phellinus igniarius , and fruiting bodies of Auricularia auricular , Tremella fuciformis , and Ganoderma lucidum have QS inhibitory activity [69,70,71,72,73,74]. Fungal QSIs were reported in the genera Penicillium and Trichoderma : polyhydroxyanthraquinones, penicillic acid, and patulin from P. restrictum , P. radicicola , and P. coprobium , respectively [68,75]; and carot-4-en-9,10-diol from T. virens [76].…”
Section: Resultsmentioning
confidence: 99%
“…The C. violaceum CV026 is a mutant strain incapable of producing AHL and violacein. It is a versatile and easy-to-use reporter that responds to exogenous AHLs and is widely used in quorum sensing inhibition assay [21,22,23,24]. The strain is also used for checking antibacterial activity [25].…”
Section: Introductionmentioning
confidence: 99%
“…The only reports so far of possible anti-QS activity are from two plant root-associated fungi, i.e. , Phialocephala fortinii and Meliniomyces variabilis [23] that are able to interfere with the N-acylated homoserine lactone regulatory system of several Gram-negative bacteria, and of Phellinus igniarius [24] and Ganoderma lucidum [25] that can suppress violacein production of Chromobacter violaceum .…”
Section: Resultsmentioning
confidence: 99%